2015
DOI: 10.1159/000430405
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Fructose Causes Gender-Different Metabolic and Vascular Dysfunction in Rats: Modulatory Effects of Resveratrol

Abstract: Background/Aims: There is limited knowledge on the gender differences in the effects of dietary fructose. In the current study, we investigated whether long-term fructose intake impacts metabolic parameters and vascular reactivity differently between male and female rats. Moreover, we tested whether resveratrol has a gender-specific effectiveness on the alterations. Methods: Male and female rats were divided into four groups as control; resveratrol; fructose and resveratrol plus fructose. Fructose was given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 33 publications
5
47
1
7
Order By: Relevance
“…It has been reported that endothelium-derived NO is a predominant mediator of endothelial-dependent relaxation in aortae, and its bioavailability is impaired in several pathophysiological states such as hyperlipidemia, metabolic syndrome, diabetes and hypertension (35,36). There is increasing evidence that high fructose induced endothelial dysfunction is associated with the decreased NO bioavailability in the vasculature (8,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that endothelium-derived NO is a predominant mediator of endothelial-dependent relaxation in aortae, and its bioavailability is impaired in several pathophysiological states such as hyperlipidemia, metabolic syndrome, diabetes and hypertension (35,36). There is increasing evidence that high fructose induced endothelial dysfunction is associated with the decreased NO bioavailability in the vasculature (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our study, nitrotyrosine was detected to indirectly indicate ROS mediated NO inactivation and peroxynitrite formation. It has been reported that fructose-fed rats exhibited a decreased expression of eNOS and p-eNOS in several tissues including aorta (8,42,43). In addition fructose has been demonstrated to generate peroxynitrite through increased superoxide production and enhanced methyglyoxal formation (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SIRT1 activator resveratrol (RSV) attenuated vascular endothelial inflammation and improved vascular function by inducing autophagy [11, 12], while SIRT1 inhibitor sirtinol promoted the inflammatory response of human THP-1 cells through inhibition of autophagy [13]. A recent study showed that fenofibrate prevented high glucose-induced inflammatory response in cardiac myoblasts by upregulating SIRT1-mediated autophagy [14].…”
Section: Introductionmentioning
confidence: 99%